Evaluasi Rasionalitas Penggunaan Antihipertensi pada Pasien Geriatri di RSUD Dr. H Bob Bazar, SKM Lampung Selatan - Herawati, Nenti; Saputri, Gusti Ayu Rai; Yasir, Angga Saputra (Journal of Islamic Medicine, 2021)
Background: Hypertension is a condition characterized by an increase in blood pressure 140/90 mmHg. Hypertension is an important risk factor for causing other cardiovascular diseases. Evaluation of the use of antihypertensive drugs aims to ensure the rational use of drugs in patients with hypertension. Objective: This study aims to determine the rationality of the use of antihypertensive drug in geriatric patients at RSUD Dr. H. Bob Bazar, SKM Lampung Selatan in terms of the correct diagnosis, the right indication, the right drug, the right dose, the right way of giving, the right time interval for giving and the right patient. Methods: This study is a non-experimental type of research in the sense that it does not provide any treatment to the research subjects and used retrospective data, namely medical record sheetsof hypertension patients in 2019. Of the total 423 medical records of hypertension patients, 51 medical records were used as research samples. The data obtained were then compared using the JNC VIII literature and the Geriatric Dosage Handbook (Lexicomp Drug Reference). Results: The results showed that the rationality of the use of antihypertensives in geriatric patients in RSUD Dr. H. Bob Bazar, SKM Lampung Selatan, is 100% accurate on diagnosis, 100% right on indication, 100% right on drug, 94.12% right on dose, 100% right on route of administration, 96.08% right on time interval and 100% right on patient. Conclusion: The percentage value of rational used of antihypertensive drugs in geriatric patients is 96,8%.Keyword : Evaluation, Hypertension, Geriatric Rationality,